God's not dead : evidence for God in an age of uncertainty - Broocks, Rice (Nashville : Thomas Nelson, 2013)
Explores "the questions surrounding faith, skepticism, and the meaning of life ... as well as ... evidence for the existence of God and the truths of Christianity"--Dust jacket flap.
Ground Zero of faith -- God's not dead -- Real faith isn't blind -- Good and evil are no illusions -- There was a beginning -- Life is no accident -- Life has meaning and purpose -- Jesus and the Resurrection -- The witness of scripture -- The grace effect -- Living proof -- Seeking God.
Includes bibliographical references (pages 243-263) and index.
Keywords: God -- Proof; God (Christianity); Apologetics